The Effect of Septoplasty on Pulmonary Functions - ابراهيم, مصطفى; يوسف, يوسف; هلال, فايز (Latakia University Journal -Medical Sciences Series, 2021)
Objectives: The objectives of this study were to assess the changes in pulmonary function after surgical correction of deviated nasal septum for nasal obstruction. Methods: A total of 81 patients with DNS with the complaints of nasal obstruction underwent septoplasty were involved in this before-after prospective study. Demographic data, clinical and physical examination including anterior and posterior rhinoscopy was performed. Pre- and post-surgery (after 1 and 3 month) spirometry was done on these patients. FVC, FEV1, PEFR, FEF25-75% and the ratio of FEV1 to FVC were the parameters measured. And the results were analyzed using various statistical tools for difference in spirometry findings depending on age group, gender, smoking and duration of disease. Results: Postoperative all PFT values, except for FEV1/FVC% value, were significantly higher than the preoperative values. Postoperative FEV1/FVC% value was significantly lower than preoperative value. The improvement was more in younger age groups, and it was more in nasal obstruction of shorter duration. There was no significant difference in improvement among males and females or among smoker and non-smokers. Conclusion: These findings suggest that septoplasty has a positive effect on pulmonary functions improvement in patients with nasal obstruction due to deviated nasal septum. And this improvement may be affected by age and the duration of obstruction, but not related to gender or smoking.